2018
DOI: 10.29024/aogh.19
|View full text |Cite
|
Sign up to set email alerts
|

Health Education Advanced Leadership for Zimbabwe (Healz): Developing the Infrastructure to Support Curriculum Reform

Abstract: An economic crisis in Zimbabwe from 1999–2009 resulted in a shortage of faculty at the University of Zimbabwe College of Health Sciences (UZCHS) and declining enrollment and graduation rates. To improve proficiency and retention of graduates, the college sought to develop a competency-based curriculum using evidence-based educational methodologies. Achievement of this goal required a cadre of highly qualified educators to lead the curriculum review and innovation processes. The Health Education Advanced Leader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…We included a broad category of technical, public health or health systems topics (33%) to capture a range of quite specific topics that appeared in some LDPs, such as curriculum development ( Aagaard et al , 2018 ), stigma of mental illness ( Abdulmalik et al , 2014 ), biostatistics ( Kebede et al , 2010 ; Matovu et al , 2011 ) or an update on HIV/AIDS ( Nakanjako et al , 2015 ). These topics were grouped together because they were considered specifically technical, rather than relating to broader leadership or management issues, and often related to the particular context in which the LPD was taking place in.…”
Section: Resultsmentioning
confidence: 99%
“…We included a broad category of technical, public health or health systems topics (33%) to capture a range of quite specific topics that appeared in some LDPs, such as curriculum development ( Aagaard et al , 2018 ), stigma of mental illness ( Abdulmalik et al , 2014 ), biostatistics ( Kebede et al , 2010 ; Matovu et al , 2011 ) or an update on HIV/AIDS ( Nakanjako et al , 2015 ). These topics were grouped together because they were considered specifically technical, rather than relating to broader leadership or management issues, and often related to the particular context in which the LPD was taking place in.…”
Section: Resultsmentioning
confidence: 99%
“…Studies indicated that maintaining a consistent stream of participants was difficult. Many studies reported that registrants dropped out potentially because HRCB initiatives distracted them from original duties, while other studies revealed that there was a small number of staff and projects in FCASs to engage local participants, potentially due to staff turnover and the lack of a financial incentive to contribute to HRCB interventions [ 39 , 41 , 45 , 48 , 49 , 52 , 55 , 56 , 58 ]. Securing and maintaining local funding for HRCB initiatives was also considered a logistical challenge across FCASs.…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported that HRCB programmes were largely driven by funding from the Global North given the limited resources within FCASs, yet following implementation of HRCB, this scarcity in local funding led to limitations in follow-up and long-term support [ 40 , 41 , 44 , 49 , 52 , 53 , 57 ]. In addition, time allocated to conduct HRCB intervention was often less than adequate [ 41 , 44 , 46 , 47 , 49 , 51 , 53 ]; one particular study highlighted the risk of having week- or month-long programmes fall under “helicopter ethnography” and “voluntourism” [ 46 ], where HIC researchers engage in rapid, temporary, and often self-serving activities in LMICs without planning for or building long-term relationships in LMICs. Additionally, the use of technology such as tablets to expand access to HRCB initiatives was problematic without adequate training [ 45 , 49 , 51 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, the University of Zimbabwe, College of Health Sciences (UZCHS) was in the process of a comprehensive curriculum review and transition to a competency based curriculum (6). As part of this review, the Department of Psychiatry sent four of its faculty members to join a UZCHS curriculum review training programme called 'Health Education and Leadership for Zimbabwe'(HEALZ) (7). As an assignment for this programme, a comprehensive needs assessment was done, and a curriculum was developed in Forensic Psychiatry.…”
Section: Introductionmentioning
confidence: 99%